(3bhGfjf GdCMhGd GdTNUjI dOi GdWhGFa GdESdGejI h GdeSjMjI JTQjYG habgG h bVGA (B/s - (3jGZj, CcQes ((3dHfGf (B:s (3ecJHI Rjf GdMbhbjI h GdCOHjI T(B. (3e(B. (3e ,s, 2008)
(3cJGH CcQe jGZj eQLYG GSGSjG dOQGSI bhGfjf GdCMhGd GdTNUjI h efgLG dCHMGK eSJbHdjIs
(3HHdjhZQGajG (B: (3U(B.247-252s
Keywords: (3GdESdGes; (3GdMbhbs; (3bhGfjf GdCMhGd GdTNUjI s